Bimetallic titanium complex catalyzed enantioselective oxidation of thioethers using aqueous H2O2 as a terminal oxidant1. Issue 59 (28th June 2015) - Bera, Prasanta Kumar; Gupta, Naveen; Abdi, Sayed H. R.; Khan, Noor-ul H.; Kureshy, Rukhsana I.; Bajaj, Hari C.
<x xml:space="preserve">Abstract</x> This study represents a highly efficient sulfide oxidation catalytic system using a non-toxic Ti-catalyst and environmentally benign aqueous hydrogen peroxide.